Epidemiology of hallucinogen use in the U.S. results from the National epidemiologic survey on alcohol and related conditions III. (February 2019) - Shalit, Nadav; Rehm, Jürgen; Lev-Ran, Shaul
Abstract: Background: Population-based data regarding the epidemiology of hallucinogen use and co-occurring psychiatric disorders is largely absent from the literature. We aim to present findings on the prevalence, sociodemographic correlates, psychiatric comorbidity, treatment utilization, social support and associated disability of hallucinogen use using nationally representative data. Method: We analyzed data from the National Epidemiologic Study on Alcohol and Related Conditions-III (2011–2012, N = 36, 309). We conducted multivariate logistic regression analyses in unadjusted and adjusted models in order to explore the odds of psychiatric disorders and associated disability among hallucinogen users. Results: Prevalence of twelve-month and lifetime hallucinogen use was 0.62% and 9.32%, respectively. Hallucinogen use was found to be significantly associated with mood disorders, anxiety disorders, eating disorders, personality disorders and substance use disorders. Following adjustment, significant associations were retained with several substance use disorders (adjusted odds ratio (AOR) for heroin use disorder = 4.89 (95% CI, 1.90–12.58), personality disorders (AOR = 2.10 (95% CI, 1.81–2.44)), Post-Traumatic Stress Disorder (AOR = 1.86, 95% CI 1.00–3.45) and past suicide attempts (AOR = 1.49, 95% CI 1.21–1.85). Conclusions: Lifetime hallucinogen use in the US is prevalent and highly comorbid with other substance use and psychiatric disorders. Hallucinogen Use Disorder is relatively uncommon, with a low risk of development following exposure to hallucinogens. There are significant associations between hallucinogen use and substance use disorders, personality disorders, PTSD and past suicide attempts. The evolving therapeutic utility of this class of substances requires further assessment of short- and long-term risks of use, before large scale clinical application is pursued.